A study of factors affecting the knowledge of Janani Shishu Suraksha Karyakram among health workers in rural block Shirur of Pune district, Maharashtra - Jadhav, Yallapa U.; Surwade, Jitendra B.; Kalyankar, Ganesh (International Journal Of Community Medicine And Public Health, 2017)
Background: Government of India launched the Janani Shishu Suraksha Karyakram (JSSK) on 1st June 2011, a new national initiative, to make better health facilities for women and child. The scheme is estimated to benefit more than 12 million pregnant women who access govt. health facilities for their delivery. The objective was to study the factors affecting the knowledge of Janani Shishu Suraksha Karyakram (JSSK) among health workers in rural block Shirur. Methods: A cross-sectional study was conducted among health workers in field practice area of rural block Shirur which is the rural field practice area of B J Government Medical College, Pune. It consists of 9 primary health centers and total 43 subcenters. A pilot study was conducted before initiating the study and the proforma was tested. The data was collected during the weekly meeting at primary health center. All the health workers were given prior information regarding the day of interview. The information regarding the knowledge of JSKK was recorded on the pre-structured and pre-tested proforma was recorded. The detail information regarding of the health workers, duration of service, educational status and training of JSSK etc. was recorded. Results: About 34.64% health workers were having excellent knowledge whereas 46.53% of health workers were having adequate knowledge of JSSK. The age distribution of health workers according to knowledge showed no statistically significant association with knowledge. Among the female health workers majority were having excellent and adequate knowledge and difference observed in knowledge was statistically significant. Among the ANM only one was having poor knowledge of JSSK. Out of 16 LHV, 10 were having excellent knowledge. Majority of the health workers with less than 10 years of service were having excellent and adequate knowledge. Excellent and adequate knowledge was statistically significantly associated with the training status of the health workers. Conclusions: Female health workers (ANM and LHV) were having better knowledge as compared to other health workers. The training status of health worker has impact on their knowledge of JSSK.